THE RELATIONSHIPS BETWEEN COMPRESSIVE STRENGTH AND DENSITY OF POLYSTYRENE LIGHTWEIGHT CONCRETE AND THEIR COMPONENT RATIOS - Al-lami, Mohammed; Al-saadi, Emad (Journal of Applied Engineering Science, 2020)
The research deals with the properties of lightweight concrete, made from polystyrene, cement, sand and water, namely the compressive strength and density. This type of lightweight concrete is characterized by thermal insulation, low density and good compressive strength compared to other types of lightweight concrete. It is used as a lining material in inclination surfaces and in the production of unloaded building units and elements. The aim of this paper is to develop mathematical relationships between compressive strength and density of concrete and their mix proportions such as sand to cement ratio (S/C), water to cement ratio (W/C) and polystyrene to cement ratio (P/C). An intensive experimental program has been conducted. From the results of the tests, a mathematical relationships were suggested to find the proportions of components based the required compressive strength and dry density.